Urban Inequality and Segregation in Europe and China Towards a New Dialogue - Pryce, Gwilym; Wang, Ya Ping.; Chen, Yu.; Shan, Jingjing; Wei, Houkai; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2021)
This open access book explores new research directions in social inequality and urban segregation. With the goal of fostering an ongoing dialogue between scholars in Europe and China, it brings together an impressive team of international researchers to shed light on the entwined processes of inequality and segregation, and the implications for urban development. Through a rich collection of empirical studies at the city, regional and national levels, the book explores the impact of migration on cities, the related problems of social and spatial segregation, and the ramifications for policy reform. While the literature on both segregation and inequality has traditionally been dominated by European and North American studies, there is growing interest in these issues in the Chinese context. Economic liberalization, rapid industrial restructuring, the enormous growth of cities, and internal migration, have all reshaped the countryprofoundly. What have we learned from the European and North American experience of segregation and inequality, and what insights can be gleaned to inform the bourgeoning interest in these issues in the Chinese context? How is China different, both in terms of the nature and the consequences of segregation inequality, and what are the implications for future research and policy? Given the continued rise of China$1 (Bs significance in the world, and its recent declaration of war on poverty, this book offers a timely contribution to scholarship, identifying the core insights to be learned from existing research, and providing important guidance on future directions for policy makers and researchers.s
Introduction -- Part I: Lessons from Europe -- Re-theorising spatial segregation: A European perspective -- Income inequality and residential segregation in European cities -- The role of migration costs in residential sorting -- Part II: Urban inequality and segregation in China -- Research on residential segregation in Chinese cities -- Urbanisation, migration and the anti-poverty programme in China -- Urban villages, their redevelopment and implications for inequality and integration -- Renovation of Shantytowns and construction of new communities -- Public service provision in China: Towards a more equal access system -- Housing policies for rural migrant workers in China -- Part III: Future directions for research and policy -- Multi-scale inequality and segregation: Theory and estimation -- Characterising social integration between rural migrants and local residents in urban China -- Social frontiers: Estimating the spatial boundaries between residential groups and their impacts on crime -- Deprivation indices in China: Establishing principles for application and interpretation -- Future directions for research on residential segregation and inequality in China.
Keywords: Geography; Social structure; Equality; Sociology, Urban; Regional economics; Spatial economics; Human geography; Regional Geography; Social Structure; Urban Sociology; Regional and Spatial Economics; Regional Geography; Human Geography